2011
DOI: 10.1021/jp109983x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Affinity of Al13: A Correlated Electronic Structure Study

Abstract: Neutral and anionic 13-atom aluminum clusters are studied with high-level, fully ab initio methods: secondorder perturbation theory (MP2) and coupled cluster theory with singles, doubles, and perturbative triples (CCSD(T)). Energies and vibrational frequencies are reported for icosahedral and decahedral isomers, and are compared with density functional theory results. At the MP2 level of theory, with all of the basis sets employed, the icosahedral structure is energetically favored over the decahedral structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…This is a normal consequence of geometries optimized under constraints, i.e., in this case the B-DNA conformation. Imposing constraints on a structure to retain a specific conformation or symmetry usually results in small negative frequencies as reported by Smith and Gordon 55 for the calculation of neutral and anionic clusters of Al 13 . Though these (A 2 , A 2 •+ , A 8 and A 8 •+ ) have small negative frequencies, the overall features of these spectra are similar to those computed with fully optimized A 2 and A 2 •+ , see Figures 6 and S12.…”
Section: Vibrational Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…This is a normal consequence of geometries optimized under constraints, i.e., in this case the B-DNA conformation. Imposing constraints on a structure to retain a specific conformation or symmetry usually results in small negative frequencies as reported by Smith and Gordon 55 for the calculation of neutral and anionic clusters of Al 13 . Though these (A 2 , A 2 •+ , A 8 and A 8 •+ ) have small negative frequencies, the overall features of these spectra are similar to those computed with fully optimized A 2 and A 2 •+ , see Figures 6 and S12.…”
Section: Vibrational Analysismentioning
confidence: 88%
“…34 This delocalized nature of hole distribution is supported from several experimental and theoretical efforts. 7,8,26,28,29,33,48,5557 These calculations were done for gas phase systems and lack the environmental effects such as hydrogen bonding and solvent induced polarization which further affect the hole delocalization in A-stacks. However, our earlier study 34 on adenine dimer radical cation in the presence of several water molecules showed that spins were still delocalized in the ratio 73% and 27%.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44][45][46] It includes also a number of theoretical studies on the structural aspects of Al clusters, [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and about their interaction [65][66][67][68][69][70][71][72] and reaction [73][74][75][76][77][78][79] with simple molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the spatial configurations of the clusters are influenced by the electronic arrangement. 31,32 The energy difference between the lowest-energy and low-lying structures (ΔE) and the Al-B bond length (R Al-B ) of Al 13 B n ±m (n = 1-6 and m = 0, 1) clusters are listed in Table II. Overall, the shortest Al-B bond length is 1.971 Å, and the longest Al-B bond length is around 2.690 Å for Al 13 B n ±m clusters.…”
Section: Stable Geometric Structuresmentioning
confidence: 99%